When vortices and cusps meet - Navarrete, Francisco Oscar (2015)
After being overlooked for decades, the presence of quantum vortices in atomic ionization processes was recently uncovered both theoretically and experimentally. On the other hand, the electron capture to the continuum cusp is one of the most conspicuous and well-studied features of the multiple differential cross section in the ionization of atoms by the impact of positively charged projectiles. Here we analyze the conditions for these two structures to approach each other in the configuration space of the transition matrix element, and the effects that this encounter might produce.